Paradoxes of digital resilience: asymmetry of regional development and local well-being in the context of crisis management - Kruhlov, Vitalii (Theory and Practice of Public Administration, 2026)
The study provides a comprehensive assessment of the relationship between the level of digital transformation and local well-being in Ukrainian regions under martial law, while also substantiating differentiated approaches to state regional policy formation based on spatial clustering. The research design relies on a combination of statistical and spatial analysis methods. The empirical basis consisted of a 2024 dataset covering 22 regions of Ukraine (specifically, the Digital Transformation Index and the Local Well-Being Index). Correlation analysis (Pearson and Spearman coefficients) was applied to test the hypothesis of a linear or monotonic relationship. For the spatial typologization of territories, the k-means clustering method with preliminary data standardization (Z-Score) was utilized. According to the correlation analysis results (r = 0.255; ρ = 0.353 at p > 0.05), the absence of a direct linear relationship between the pace of public sector digitalization and the objective state of societal comfort was statistically proven. The existence of the «digital resilience» phenomenon was empirically confirmed, wherein under security crises, digitalization transforms from a tool for enhancing well-being into a fundamental mechanism for the institutional survival of local self-government. Based on the cluster analysis, regions were differentiated into four typological groups: «Leaders of balanced development», «Regions of digital deficit», «Regions of digital paradox» (high digitalization combined with negative well-being), and «Territories of complex vulnerability». The ineffectiveness of applying universal strategies in public administration was demonstrated. An adaptive approach to the allocation of public finances has been developed, which proposes cluster-specific regulatory instruments: from innovation stimulation based on public-private partnerships in rear regions to direct anti-crisis financing of critical services and the deployment of mobile solutions in frontline areas.